Sentencing Based on the Principle of Justice for Victims of Serious Crimes Committed By Minors - Ngurah Suradatta Dharmaputra (Asian Journal of Social and Humanities, 2026)
This study examines sentencing based on the principle of justice for victims of serious crimes committed by children in the juvenile criminal justice system in Indonesia. Through Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, Indonesia places child protection, rehabilitation, and restorative justice as the main orientation, with prison sentences for children being limited to at most half of the criminal threat for adults. However, in cases of serious crimes such as murder, rape, and other violent crimes, these arrangements often create gaps in realizing substantive justice for victims and their families. This study used normative legal methods with legislative, conceptual, and comparative legal approaches, especially by comparing the Indonesian and United States systems that recognize certain case transfer mechanisms so that child offenders can be tried as adults based on certain criteria. The results of the study show that the Indonesian legal system does not have legal flexibility in responding to serious crimes committed by children, thus causing public dissatisfaction and the perception of injustice. Therefore, this study offers a dual-track criminal model that balances child protection with victim rights through a case-by-case assessment. The proposed criteria include the severity of the crime, previous criminal history, mental maturity, and public safety considerations. Reformulation of penal policies against child perpetrators of serious crimes is needed to realize proportionate sanctions without ignoring the principles of child protection and rehabilitation.